Polacy w życiu muzycznym Kazania do 1915 roku - Garczyk, Bartłomiej (Przegląd Wschodnioeuropejski, 2025)
Kazan was an important administrative, scientific and cultural center. There were numerous theaters in the city area where opera and operetta plays where staged There were also professional and amateur musical institutions. In addition to Russians and Tatars, Kazan was also inhabited by a polish colony, among which there were many students, academic lecturers and representatives of free professions. There was also a large group of music teachers, vocal and dance educators, as well as composers and artists who left a visible mark on the musical and cultural life of the capital of Volga Region.